FUNDAMENTAL PRINCIPLE OF INTERNATIONAL HUMAN RIGHT LAW-BASIS FOR THE RIGHT TO LIFE OF THE UNBORN CHILD (UUM Journal of Legal Studies, 2014)
The contention that an unborn child has the right to life has been visited with several oppositions from all works of life, all over the world. Most people do not accept the view that an unborn child possesses any form of human right which is to be protected because, that child is yet to be born into the world. It is however an established fact that, the fundamental principle of international human right instrument is to uphold the dignity and sanctity of all human persons, whether born or unborn. This shows that international human right instruments are founded on the basis of natural law. This study set out to investigate the core principle of international human right law. By so doing, the actual values and tenents of international human right law will be revealed. This is a doctrinal research, wherein the authors set out on a fact finding mission using selected articles, books and periodicals to bring out the objective of the study. At the end of the exercise, it was revealed that no international human right law will perpetrate a principle in opposition to natural law. This being the case, the unborn child, like any other living being is vested with the inalienable right to life.Keywords: Natural law, international human right law, right to life, unborn child.